Sexual rights, religion and post-neoliberalism in Argentina (2003-2015) - Jones, Daniel Eduardo (2018)
This paper examines the relation between sexual politics and post-neoliberalism/populism in Kirchners’ Argentina between 2003 and 2015, focusing on the role of religious actors. Despite the opposition of religious leaders, including that of Archbishop Jorge Bergoglio (now Pope Francis), Argentina advanced in the recognition of gender and sexual rights during the Kirchners’ administrations. Conflicts around gender and sexuality, particularly around same-sex marriage, explain some of the tensions between political and religious actors in the period. The focus of this paper on sexual politics shows that the Kirchners’ administrations, unlike other traditional populist or post-neoliberal administrations, had a strong liberal component, which explains the tensions between that populist government and conservative religious actors.